Interrelationship of water and soil management techniques applied to millet crops: a review (Research, Society and Development, 2020)
Agriculture is facing a significant challenge worldwide due to the scarcity of water resources. The water unavailability encouraged several studies on wastewater in agriculture. Among the types of wastewater, greywater can be cited as a more viable and safe alternative, as they have a lower microbial load. Besides, for greater efficiency of water resources, the use of wastewater in agriculture may be associated with other agricultural practices, such as the reduction of irrigation depths, the use of plant species tolerant to water deficit (such as millet cultivation) and balanced nutritional management value provided by organic fertilization. Most of the information about millet cultivation techniques are essential for success in areas with low water availability, such as the Brazilian semiarid region. Thus, this review aims to present alternative management techniques (water reuse, deficit irrigation, and organic fertilization) that used in association with the millet culture (Pennisetum glaucum (L.) R. Br.) aiming for an increase in productivity with efficient use of water. Several types of research were carried out in databases (ScienceDirect, Scopus, Mendeley, and Google Scholar) without language restriction, with the literature of significant relevance in Agricultural Sciences. The association of reduced irrigation volumes with organic fertilization is an alternative that improves the efficiency of water use in millet and, consequently, its production during the drought periods.